Production of synthetic fuels by high‐temperature co‐electrolysis of carbon dioxide and steam with Fischer‐Tropsch synthesis. (28th February 2016) - Frost, Lyman; Elangovan, Elango; Hartvigsen, Joseph
Abstract : Numerous entities are currently involved in the production of synthetic fuels using various feedstock options including natural gas, refuse derived fuel, landfill gas, anaerobic digester gas, coal, and mixtures of these inputs. Current world‐class FT plants (∼15 900 m 3 /d or 100 000 barrels per day) require large deposits of natural gas (i.e. ∼1.78 m 3 /L/d or 10 MSCF/BPD means gas sources that can provide ∼10 billion m 3 per year for plant lifetime). Modular Fischer‐Tropsch (FT) reactors currently under development have some unique features that reduce cost and provide the ability to utilize sources of natural gas, biomass, or other under‐utilized sources of energy that would otherwise not be developed. The current Ceramatec modular FT reactor operates with a fixed bed size of 10 cm diameter using an internal heat transfer structure to keep axial and radial temperature variation to < 10 °C. The internal heat transfer media avoids the traditional problem with fixed bed reactors of heat removal from highly exothermic reactions. These reactors can also be used to mitigate the current concern with emissions of carbon dioxide when used in conjunction with high‐temperature co‐electrolysis (HTCE) of carbon dioxide and water to produce synthesis gas and subsequently synthetic fuels. When combined with a non‐carbon source of electricity such as wind, solar, biomass gasification, or anaerobic digester gas, it is possible to store intermittent sources of electricity as liquid fuels for later use. The HTCE generally operates at a voltage of 1.32 V and a current density of ∼300 mA/cm 2 .